2004
DOI: 10.1016/j.physrep.2004.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Regularities of many-body systems interacting by a two-body random ensemble

Abstract: The ground states of all even-even nuclei have angular momentum, I, equal to zero, I = 0, and positive parity, π = +. This feature was believed to be a consequence of the attractive short-range interaction between nucleons. However, in the presence of two-body random interactions, the predominance of I π = 0 + ground states (0 g.s.) was found to be robust both for bosons and for an even number of fermions. For simple systems, such as d bosons, sp bosons, sd bosons, and a few fermions in single-j shells for sma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(54 citation statements)
references
References 101 publications
(322 reference statements)
0
54
0
Order By: Relevance
“…Our calculations are partly based on the shell-model code Oxbash [10]. The square roots s α (J) for 20 Ne are shown in Fig. 3, those for 24 Mg are shown in Fig.…”
Section: )mentioning
confidence: 99%
See 2 more Smart Citations
“…Our calculations are partly based on the shell-model code Oxbash [10]. The square roots s α (J) for 20 Ne are shown in Fig. 3, those for 24 Mg are shown in Fig.…”
Section: )mentioning
confidence: 99%
“…Subsequent work showed that similar regularities exist in bosonic [17] and electronic [18] many-body systems with two-body interactions. The phenomenon of spin-zero preponderance seems a robust and rather generic feature which has received much attention since, see the reviews [19,20] and references therein. Here we discuss it in the framework of our representation (9) of the Hamiltonian of the TBRE.…”
Section: B Preponderance Of Ground States With Spin Zeromentioning
confidence: 99%
See 1 more Smart Citation
“…The randomness of matrix elements of the nuclear shell model Hamiltonian is an interesting topic [81][82][83]. Shen et al studied the general behavior of matrix elements of the nuclear shell model Hamiltonian [84].…”
Section: Randomness Of Matrix Elements Of the Nuclear Shell Model Hammentioning
confidence: 99%
“…The observation of a statistical preference of L = 0 ground states for ensembles of random two-body interactions has sparked a large number of investigations to further explore the properties of these random systems and to understand the mechanism for the emergence of regular ordered spectral features from random interactions [6][7][8][9]. The appearance of ordered spectra in systems with chaotic dynamics is a robust property that does not depend on the specific choice of the (two-body) ensemble of random interactions [2,[10][11][12], timereversal symmetry [10], and the restriction of the Hamiltonian to one-and two-body interactions [13], nor is it limited to yrast states with small angular momentum L = 0, 2, 4 [14] as used in the original studies [2,3].…”
Section: Introductionmentioning
confidence: 99%